Coping with Adversity Regional Economic Resilience and Public Policy - Wolman, Harold (Cornell University Press, 2017)
Coping with Adversity addresses the question of why some metropolitan-area regional economies are resilient in the face of economic shocks and chronic distress while others are not. It is particularly concerned with what public policies make a..
Description based on publisher supplied metadata and other sources
Keywords: United States--Economic conditions--20th century--Regional disparities